Endotherapy for pancreatic necrosis: An update. Issue 1 (7th December 2018) - Jha, Ashish K; Goenka, Mahesh K; Kumar, Ramesh; Suchismita, Arya
Abstract : Approximately 20% of patients with acute pancreatitis develop pancreatic necrosis. The presence of necrosis in a pancreatic collection significantly worsens the prognosis. Pancreatic necrosis is associated with high mortality and morbidity. In the last few decades, there has been a significant revolution in the treatment of infected pancreatic necrosis. A step‐up approach has been proposed, from less invasive procedures to the operative intervention. Minimally invasive treatment modalities such as endoscopic drainage and necrosectomy, percutaneous drainage, and minimally invasive surgery have recently replaced open surgical necrosectomy as the first‐line treatment option. Endoscopic intervention for pancreatic necrosis is being increasingly performed with good success and a lower complication rate. However, techniques of endotherapy are still not uniform and vary as per local expertise, and there are still many unresolved questions with regard to the interventions in patients with pancreatic necrosis. The objective of this paper is to critically review the literature and update the concepts of endoscopic interventional therapy of pancreatic necrosis. Abstract : Pancreatic necrosis is associated with high mortality and morbidity. Here, we review the literature and update the concepts of endoscopic therapy of pancreatic necrosis.